Penggunaan Youtube Sebagai Media Pembelajaran dalam Persiapan Siswa Menghadapi Dunia Kerja - Ummi Masrufah Maulidiyah; andini dwi arumsari (Universitas Narotama, 2021)
The use of youtube as a learning media has been widely used by the community, especially by students. One of the uses of youtube as a learning media is to prepare students for the world of work. The purpose of this study is to describe how the use of youtube as a learning medium to prepare students for the world of work. This research is a descriptive research sourced from reference journals and articles as well as other sources obtained from books. The results of this study are the use of youtube as a learning medium is often used by students as a source of information for preparation in the world of work. By using youtube learning media, students can get various information about their preparation in the world of work. For example, making a good curriculum vitae, preparing for job interviews, making good time management so that work can be completed, and other soft skills that can support students in preparing themselves to enter the world of work. Key words: teaching aids, world of work, youtube